Effect of Cultivar and Nutrient Medium on In Vitro Shoot Formation on Capitulum Explants of Gerbera (Gerbera jamesonii Bolus) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to examine the shoot formationcapacity of the capitulum explants of some gerbera cultivars in differentnutrient media. Immature capitulum explants of the gerbera cultivarsAmeretto, Red Bull, Ruby Red and Yanara were cultured on Pierikmedium (P) with different concentrations of benzyladenine (BA) andRadice and Marconi medium (RM). The main P and RM media were usedeither in liquid form using cotton wool as support or solidified with agar.There was a significant interaction between the different media and thegerbera cultivars in all the parameters measured. The gerbera cultivarsshowed different responses to various media compositions with regard toshoot formation on the capitulum explant.There was a general increase invitrification rate with the increase in the BA concentration in the medium.Shoots formed in liquid media showed a high vitrification rate.
Keywords: Benzyladenine; capitulum; Gerbera jamesonii; vitrification